Leveraging off-target reads in panel sequencing for homologous recombination repair deficiency screening in tumor - Ball, Markus; Ourailidis, Iordanis; Kluck, Klaus; Menzel, Michael; Kirchner, Martina; Allgäuer, Michael; Tay, Timothy Kwang Yong; Schnecko, Fabian; Volckmar, Anna-Lena; Goldschmid, Hannah; Neumann, Olaf; Fröhling, Stefan; et al. (The journal of molecular diagnostics, 2024)
Targeted tumor only sequencing has become a standard practice in cancer diagnostics. This study aims to develop an approach for robust copy number variant calling in tumor samples using only off-target region (OTR) reads. We also established a clinical use case for homologous recombination deficiency (HRD) score estimation (HRDest) using the sum of telomeric-allelic imbalance and large-scale state transition scores without the need for loss of heterozygosity information. A strong correlation was found between HRD score and the sum of telomeric-allelic imbalance + large-scale state transition in The Cancer Genome Atlas cohort (ρ = 0.99, P < 2.2 × 10−16) and in a clinical in-house cohort of 34 tumors (ρ = 0.9, P = 5.1 × 10−13) comparing whole-exome sequencing and targeted sequencing data. HRDest scores from 1086 clinical cases were compared with The Cancer Genome Atlas data set. There were no significant differences in HRD score distribution within the analyzed tumor types. As a control, commercially available HRD standards were also sequenced, and the HRDest scores obtained from the OTR reads were well within the HRD reference range provided by the manufacturer. In conclusion, OTR reads of tumor-only panel sequencing can be used to determine genome-wide copy number variant profiles and to approximate HRD scores.
Online verfügbar: 22. März 2024, Artikelversion: 16. Mai 2024
Gesehen am 22.07.2025